COMPUTERED NOMERIC CONTROL FOR IMPRISED CYRCOID PLATES (REMUNOM, 2025)
The Computer Numerical Control (CNC) has been consolidated as a precision technology widely used in the manufacturing processes of complex parts. In the context of the production of printed circuit plates (PCBs), precision in machining is essential, especially for surface assembly components (SMD) that require strict tolerances. This article describes the development of a three-axis CNC machine, designed to machine PCBs with high precision, in order to meet the needs of low-cost prototyping. The machine is controlled by an Arduino system and uses CAD and CAM softwars for production control, integrating the G-code language to ensure the accuracy of the movements.